2016
DOI: 10.3892/etm.2016.3893
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 suppresses gastric cancer cell proliferation and invasion via regulation of angiopoietin-2

Abstract: Novel targeted therapies need to be developed for gastric cancer, the third most common cancer type and the second most common cause of cancer-related mortality in China. Previous studies indicate that angiopoietin (Ang)-2 serves a role in the proliferation, migration, invasion and adhesion of malignant cells. The present study identified, using functional studies, that exogenous expression of miR-218 increased migration of NCI-87 and HGC-27 gastric cancer cells, which coincided with a reduction in the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…miR-218 reduces VEGF expression in prostate cancer by acting on the mTOR component RICTOR (rapamycin-insensitive companion of mammalian target of rapamycin) and by blocking the RICTOR/mTOR/HIF-1/VEGF signaling pathway [110]. In gastric cancer, two targets of miR-218 have been identified: Angiopoietin-2 and ROBO1 (roundabout guidance receptor 1); their downregulation results in a reduction of tumor proliferation, invasion, and angiogenesis [111,112]. Moreover, low levels of miR-218 result in endothelial cell sprouting, motility, and tube formation [112].…”
Section: Mir-218mentioning
confidence: 99%
“…miR-218 reduces VEGF expression in prostate cancer by acting on the mTOR component RICTOR (rapamycin-insensitive companion of mammalian target of rapamycin) and by blocking the RICTOR/mTOR/HIF-1/VEGF signaling pathway [110]. In gastric cancer, two targets of miR-218 have been identified: Angiopoietin-2 and ROBO1 (roundabout guidance receptor 1); their downregulation results in a reduction of tumor proliferation, invasion, and angiogenesis [111,112]. Moreover, low levels of miR-218 result in endothelial cell sprouting, motility, and tube formation [112].…”
Section: Mir-218mentioning
confidence: 99%
“…miR-218 is also regarded as a tumor suppressor due to its function in the inhibition of invasion and growth of nasopharyngeal (31), oral (19), lung (15,32), and bladder (33) cancer cells. By regulating the expression of Ang-2 in gastric cancer cells NCI-87 and HGC-27, miR-218 overexpression suppressed cell proliferation and angiogenesis (17). An MTT assay revealed that miR-218 overexpression markedly suppressed the proliferation of gastric cancer cells and wound scratch assays indicated that miR-218 inhibited cell migration and EMT by targeting WASF3 (30).…”
Section: Discussionmentioning
confidence: 97%
“…In cultured gastric cancer cell lines SGC7901 and BGC823, it was revealed that miR-218 mRNA and protein expression were significantly decreased compared to those in normal gastric epithelial cell line GES-1 (30). Furthermore, compared with gastric cancer cell lines MGC80-3 and HGC-27, decreased miR-218 expression levels were also found in the more aggressive gastric cancer cell line NCI-87 (17). Notably, the present study revealed a significant decrease in miR-218 expression in human colon cancer tissues and SW1417 cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MiR‐218, which is embedded in the introns of SLIT2 and SLIT3 (X. Zhang et al, ), is a tumor repressor miRNA that inhibits cell growth, invasion, migration, cancer stem‐like cell self‐renewal and angiogenesis (Tu et al, ; Uesugi et al, ; Yamasaki et al, ). Multiple studies have shown that miR‐218 is downregulated in several types of cancers (B. Guan et al, ; Tang, Wang, Zhang, & Li, ). Overexpression of miR‐218 leads to the inhibition of HUVECs migration, proliferation, and tube formation in vitro.…”
Section: Cancer Angiogenesis and Mirnasmentioning
confidence: 99%